A solidariedade no direito das obrigações - Silva, Domício Whately Pacheco e (2019)
The aim of this work is to analyze solidarity (with joint and several debtors or creditors) in the light of the 2002 Brazilian Civil Code. The conception of obligation as a process, that is, as an obligational relationship, has been adopted as a premise. After starting with the delimitation of the subject matter, brief considerations were provided on the historical origins of solidarity, since the Classical Roman law; the systematic framework of solidarity in several encodings was then described; afterwards, its assumptions (or its only assumption, as one tried to demonstrate here); its sources; its cause, function and foundation; its structure; and its (possible) categories were also presented. The legal nature of solidarity was faced, next, as a way of being of certain multi-party obligations. After dealing with the accidental elements in solidarity (condition and term), a chapter was dedicated for passive solidarity (joint and several debtors), in which one approached its concept; content; importance; fundamental effects; means of defense of the solidary debtors; and the main amending, extinguishing and impeditive facts to these obligational relationships; the chapter was closed with the internal phase, during which the old consorts may (if applicable) demand adjustment of advancements from the other obligors. Active solidarity (joint and several creditors) was then symmetrically analyzed, representing the other face of the same coin. The dissertation finishes with the approach of some procedural issues affected by solidarity: the litis consortium (optional, necessary, simple and unitary); assistance (simple and the so-called litisconsorcial); the implead; the so-called chamamento ao processo; and the res judicata (or effectiveness of the judicial sentence, depending on the conception adopted)